The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1600-0412.2011.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre‐pregnant body mass index, maternal weight change and offspring birthweight

Abstract: Objective. To estimate the association between maternal pre-pregnant body mass index (BMI) and maternal weight change during pregnancy and offspring birthweight using the BMI classification developed by World Health Organization (WHO) and adopted by the Institute of Medicine (IOM) 3), mean maternal weight change in the first 30 weeks of gestation was 9.3kg (SD 4.4), mean birthweight was 3675g (SD 487) and mean age 30.3 years. Of the women, 65.2% had a normal pre-pregnancy weight, 2.9% were underweight, 22.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 31 publications
5
28
2
1
Order By: Relevance
“…In a previous study, pre-pregnancy BMI and GWC were positively associated with offspring birth weight. 19 However, in our study and a previous adjustment for the effect mediated through birth weight attenuated the effect of GWC. 9 GWC may be linked to offspring BMI through several pathways.…”
Section: 4713contrasting
confidence: 71%
See 1 more Smart Citation
“…In a previous study, pre-pregnancy BMI and GWC were positively associated with offspring birth weight. 19 However, in our study and a previous adjustment for the effect mediated through birth weight attenuated the effect of GWC. 9 GWC may be linked to offspring BMI through several pathways.…”
Section: 4713contrasting
confidence: 71%
“…2,[10][11][12]17,18 In a previous study, we estimated the association between maternal pre-pregnancy BMI and maternal GWC with birth weight as the main outcome and found that offspring birth weight increased with both increasing maternal pre-pregnancy BMI and GWC during pregnancy in all six pre-pregnancy BMI categories based on World Health Organization (WHO) classifications. 19 It is thus important to further explore to what extent these findings are pertinent to children later in life.…”
Section: Introductionmentioning
confidence: 99%
“….should we work to understand mechanistically how birth weight and fetal growth are related to leukemia risk?" (23) Evidently maternal prepregnancy weight and pregnancy weight gain are associated with the birth weight of baby (24). Perhaps, birth weight reflects, in part, maternal circadian disruption which leads to her elevated weight.…”
Section: Circadian Gene Expression and Actionmentioning
confidence: 99%
“…As we know, it has been widely recognized that maternal pre-pregnancy body mass index (pre-BMI) and gestational weight gain are closely associated with pregnancy outcomes including neonatal birth weight (NBW) (Stamnes Koepp et al, 2012;Li et al, 2014). In 2009, the Institute of Medicine (IOM) of America introduced a guideline concerning appropriate maternal weight gain during different trimesters for singleton pregnancy, which may result in a better pregnancy outcome (Oken et al, 2009).…”
mentioning
confidence: 99%